Relationship between work overload, role conflict and supervisor support on occupational stress among nurses in northen region hospital, Malaysia - Nur Liyana, Johari (2020)
Nurses in hospitals are potentially exposed to gain occupational stress against their workplace environment. This study primary focuses on investigating the relationship between work overload, role conflict, and supervisor support on occupational stress for nurses of a hospital in northern Malaysia. A total of 110 returned questionnaires among nurses at government hospital in northen region were analysed using SPSS version 25. Pearson Correlation and Multiple Regression Analysis are used as the connection among independent and dependent variables. The results indicate that work overload, role conflict and supervisor support have a connection towards occupational stress of the nurses. At last, the theoretical and practical recommendations just as limitations and suggestions for future exploration additionally talked about in this theory.